INNOVATIVE TECHNOLOGY APPLICATION IN EDUCATION - Dilshodakhon Muminova (Bright Mind Publishing, 2025)
In light of the intense competition between the entertainment industry and the educational system, strategies are required to draw students in and engage them in the learning process. The trend in the development of virtual and augmented reality technologies indicates that in order to achieve the most logical combination of the educational process and the gaming process, educational elements—particularly those related to the course of school subjects—must be incorporated when developing applications.
Keywords: Computer technology, script, multimedia, augmented reality, and virtual reality.